A novel multi-component protein vaccine ECP001 containing a protein polypeptide antigen nPstS1 riching in T-cell epitopes showed good immunogenicity and protection in mice - Yu, Jinjie; Fan, Xueting; Luan, Xiuli; Wang, Ruihuan; Cao, Bin; Qian, Chengyu; Li, Guilian; Li, Machao; Zhao, Xiuqin; Liu, Haican; Wan, Kanglin; Yuan, Xiuqin (Frontiers in Immunology, 2023)
Tuberculosis (TB) is an infectious disease that seriously affects human health. Until now, the only anti-TB vaccine approved for use is the live attenuated Mycobacterium bovis (M. bovis) vaccine — BCG vaccine, but its protective efficacy is relatively low and does not provide satisfactory protection against TB in adults. Therefore, there is an urgent need for more effective vaccines to reduce the global TB epidemic. In this study, ESAT-6, CFP-10, two antigens full-length and the T-cell epitope polypeptide antigen of PstS1, named nPstS1, were selected to form one multi-component protein antigens, named ECP001, which include two types, one is a mixed protein antigen named ECP001m, the other is a fusion expression protein antigen named ECP001f, as candidates for protein subunit vaccines. were prepared by constructing one novel subunit vaccine by mixing or fusing the three proteins and combining them with aluminum hydroxide adjuvant, and the immunogenicity and protective properties of the vaccine was evaluated in mice. The results showed that ECP001 stimulated mice to produce high titre levels of IgG, IgG1 and IgG2a antibodies; meanwhile, high levels of IFN-γ and a broad range of specific cytokines were secreted by mouse splenocytes; in addition, ECP001 inhibited the proliferation of Mycobacterium tuberculosis in vitro with a capacity comparable to that of BCG. It can be concluded that ECP001 is a novel effective multicomponent subunit vaccine candidate with potential as BCG Initial Immunisation-ECP001 Booster Immunisation or therapeutic vaccine for M. tuberculosis infection.